Promoting the National Framework for Climate Services in Ghana Through Collaborative Effort for Sustainable Agriculture - Martey, Francisca; Clottey, Victor; Yeboah, Stephen; Tepa-Yotto, Ghislain; Nikoi, Gordon; Wilson, Michael; Dalaa, Mustapha Alasan; Damba, Osman Tahidu (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This policy briefing captures recommendations for the development and implementation of the National Framework for Climate Services (NFCS) in Ghana